Quality of YouTube™ Videos on Anterior Inciso-proximal Composite Restoration: A Content Quality Analysis - Yee Ang; Hetal AK Mavani; Fara A Adam; Jun A Chong; Laila A Hassan (Jaypee Brothers Medical Publishers (P) Ltd., 2025)
Indexed by WOS/Scopus/ERA